Changes in the chemical and sensory profile of ripened Italian salami following the addition of different microbial starters. (October 2021) - Rocchetti, Gabriele; Rebecchi, Annalisa; Dallolio, Michele; Braceschi, Gianpaolo; Domínguez, Rubén; Dallolio, Giuliano; Trevisan, Marco; Lorenzo, José M.; Lucini, Luigi
Abstract: In this work, Italian salami were produced using microbial starters ( Pediococcus pentosaceus, Lactobacillus sakei, and Staphylococcus xylosus ) and compared to a control sample (without starter). Metabolomics in combination with microbiological and sensory analyses were used to investigate the overall quality. Samples were analyzed immediately after stuffing, following 7, 30, and 45 days of ripening. Each microbial starter imposed distinctive metabolomic signatures at the end of ripening. The accumulated discriminant compounds were mainly related to lipid oxidation (including hydroxy- and epoxy derivatives of fatty acids) following the inoculation with L. sakei . However, the inoculation with P. pentosaceus resulted in the accumulation of γ-glutamyl peptides, compounds driving a kokumi-related taste. Noteworthy, our findings supported the involvement of the chemical compounds profiled in the definition of final taste and aroma. This information paves the way towards the definition of more objective and tailored starters-related flavours enhancement approaches in the sector of cured meat. Highlights: Italian salami samples were formulated by inoculating different starter cultures. Each microbial starter imposed distinctive metabolomic signatures after 45 days of ripening. Protein and lipid-hydrolysis related compounds determined the major changes. The inoculation with P. pentosaceus increased the accumulation of kukumi-related compounds. Sensory analysis showed a good overlapping degree with the metabolomic profiles.